+0  
 
0
89
1
avatar

-3/4(2x-1)=2-2x

Guest Feb 14, 2017
Sort: 

1+0 Answers

 #1
avatar+77202 
0

(-3/4)(2x-1)=2-2x    multiply both sides by 4

 

-3 (2x - 1)  = 4 ( 2 - 2x)     simplify

 

-6x + 3  = 8 - 8x      add 8x , subtract 3  to /from  both sides

 

2x  =  5       divide by 2

 

x  = 5/2

 

 

cool cool cool

CPhill  Feb 14, 2017

29 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details